NOVEL DESIGN OF CALANONE DERIVATIVES AS ANTI-LEUKEMIA COMPOUNDS BASED ON QUANTITATIVE STRUCTURE-ACTIVITY RELATIONSHIP ANALYSIS - Ponco Iswanto; Mochammad Chasani; Harjono Harjono; Iqmal Tahir; Muhammad Hanafi; Eva Vaulina YD (Universitas Gadjah Mada, 2011)
Leukemia drug discovery based on calanone compound was conducted in previous research and produced 6 calanone derivatives. Most of them have lower activities against leukemia cell L1210 than pure calanone. A Quantitative Structure-Activity Relationship (QSAR) analysis is conducted in this work to find more active calanone derivatives. Six compounds were used as the material of the research because they already have anti-leukemia activity data expressed in Inhibitory Concentration of Fifty Percent Cell Lethal (IC50, in mg/mL). Calculation of predictors was performed by AM1 semiempirical method. QSAR equation is determined using Principle Component Regression (PCR) analysis, with Log IC50 as dependent variable. Independent variables (predictors) are atomic net charges, dipole moment (m), and coefficient partition of n-octanol/water (Log P). This work recommends 3 novel designs of calanone derivatives that may have higher activities (in mg/mL) than those already available, i.e. gemdiol calanone (57.78), 2,4-dinitrophenylhydrazone calanone (30.94) and 2,4,6-trinitrophenylhydrazone calanone (18.96).